LINGUISTIC NATIONALISM IN THE BIPA 1 TEXTBOOK: REPRESENTATION OF LANGUAGE AND NATIONAL IDENTITY - Nirmalasari, Yohanna (JURNAL KONFIKS, 2025)
Textbooks are an important component of BIPA learning. In this textbook, the use of language can reflect Indonesian nationalism. Indonesian nationalism must be introduced to BIPA 1 learners because BIPA 1 learners need to obtain initial schemata and perceptions about Indonesia. This study aims to reveal the representation of the Indonesian language and the construction of national identity in the BIPA 1 textbook: Sahabatku Indonesia through the Critical Discourse Analysis (CDA) approach modeled after Norman Fairclough. This textbook not only functions as a medium for language learning but also as an ideological tool that shapes the discourse of linguistic nationalism. This study uses a qualitative approach with data analysis of verbal and visual texts, and learning tasks in five main units. The data source in this study is the BIPA level 1 textbook. This book was chosen because it is the first learning material for foreigners who want to learn Indonesian, so it must represent Indonesian values. The data in this study are dialogues, texts, and practice questions. The results of the study show two major themes: (1) Indonesian is represented as a homogeneous and official national identity, and (2) language is used as an instrument of social regulation and power relations. This representation shows that Indonesians in the BIPA 1 textbook are not neutral but ideologically charged, reflecting linguistic nationalism and Indonesia's unique social value system. Based on these findings, it can be concluded that language is part of ideological construction, not merely a tool for communication. These results reinforce the notion that the BIPA 1 textbook can serve as a space for the production of discourse that constructs specific social identities.